Visualization of Data Recipients of the Smart Indonesia Program (PIP) through the Business Intelligence Dashboard at the PSP Center - Desy Ramatika; Leni Marlina; Andysah Putera Utama Siahaan (Yayasan Sinergi Multidimensi Kreatif, 2025)
The increasing number of recipients of the Indonesia Smart Program (Program Indonesia Pintar - PIP) demands a more effective and efficient data management system. At PSP Center, conventional methods such as spreadsheets are still primarily used for recording and reporting, which may cause delays in information, input errors, and a lack of in-depth data visualization. This study aims to design and develop a Business Intelligence (BI) dashboard capable of integrating PIP recipient data from various sources and presenting it in an interactive and informative visual format. By applying the Extract, Transform, Load (ETL) process, this system is expected to improve analysis efficiency, support data-driven decision making, and strengthen transparency and accountability in the implementation of the PIP program at PSP Center.